Strategi Infrastruktur Hijau dalam Mendukung Ketahanan Lingkungan Perkotaan di Kawasan Historis Baciro, Yogyakarta: indonesia - Mistoro, Niesa Hanum; Yulianto, Andik; Rahmawati, Suphia; Putro, Muhammad Kholif Lir Widyo (Asian Journal of Innovation and Entrepreneurship, 2026)
Many urban cities in Indonesia face critical challenges such as limited green open spaces, declining environmental quality, and spatial pressure driven by rapid population growth. These conditions threaten urban environmental resilience, particularly in maintaining quality of life and sustainable resource use. This study aims to formulate adaptive green infrastructure planning strategies for the Baciro historical neighbourhood in Yogyakarta to enhance environmental quality while preserving the area’s cultural identity. A qualitative case study approach was employed, combining spatial planning documents, field observations, and stakeholder interviews. The findings indicate that despite limited open spaces, Baciro offers significant opportunities for green infrastructure development through the utilization of residual and vertical spaces, including narrow alleys, riverbanks, and commercial building façades. Proposed strategies include the implementation of vertical gardens, green corridors, revitalized riverfronts, and pedestrian-friendly green streets. These interventions contribute ecological functions—such as water infiltration, microclimate regulation, and air quality improvement—while also strengthening social cohesion through community participation. Furthermore, integrating green infrastructure with the Transit Oriented Development (TOD) concept expands its role in promoting sustainable mobility and liveable urban spaces. This research demonstrates that green infrastructure can serve as a strategic instrument for achieving urban environmental resilience while safeguarding historical heritage in the face of urbanization pressures. The results provide insights and practical implications for planning similar historic neighbourhoods across Indonesian cities that encounter comparable spatial and environmental challenges.